Chemotherapy-Induced Musculoskeletal Pain Syndrome in Breast Cancer: A Cross-Sectional Analysis of Prevalence, Predictors, and Impact on Quality of Life - Farpour, Hamid Reza; Zarei, Arash; Nasrolahi, Hamid; Ansari, Mansour; Ahmed, Faisal (Asian Pacific Journal of Cancer Care, 2026)
Introduction: Taxane-based chemotherapy is an effective treatment for breast cancer but frequently causes chemotherapy-induced musculoskeletal pain syndrome, a toxicity that significantly impairs patients’ quality of life. Despite its clinical importance, epidemiological data on this syndrome from Middle Eastern populations are limited. This study aimed to assess the prevalence, predictors, and quality-of-life impact of chemotherapy-induced musculoskeletal pain syndrome among breast cancer patients in Iran. Materials and Methods: In this cross-sectional study, 151 Iranian women with breast cancer receiving chemotherapy were enrolled. Patients were stratified by regimen: paclitaxel (n=119), docetaxel (n=9), or non-taxane controls (n=23). CHIMPS was evaluated using the validated Persian version of the McGill Pain Questionnaire (MPQ). Multivariable logistic regression was employed to identify independent predictors of severe pain (defined as a numerical rating scale score ≥8). Results: The overall prevalence of CHIMPS was 72.2% (109/151), with significant variation across regimens: 80.7% for paclitaxel, 66.7% for docetaxel, and 30.4% for non-taxane controls (χ²=29.4, p<0.001). Severe pain was more common in taxane recipients (paclitaxel: 52.1%; docetaxel: 66.7%) versus controls (28.6%; p=0.007). Key independent predictors of severe CHIMPS included docetaxel regimen (adjusted odds ratio [OR]=4.92, 95% CI: 1.87–12.93; p=0.001), pain onset within ≤2 days post-infusion (OR=3.21, 95% CI: 1.65–6.24; p=0.008), and nocturnal pain (OR=2.97, 95% CI: 1.42–6.18; p=0.004). The syndrome profoundly disrupted QOL, most notably in daily activities (95.4%), sleep (85.3%), and mobility (80.7%). Chemotherapy delays due to pain were uncommon (4.6%). Conclusions: This study identifies a high burden of CHIMPS among breast cancer patients receiving taxane-based chemotherapy. The predictors identified specific taxane agent, early pain onset, and nocturnal pain provide a clinical framework for early risk stratification and proactive management to preserve treatment adherence and quality of life.